ROLE OF PROLACTIN AND THYROID HORMONE IN PSYCHIATRIC DISORDERS - Ambad, Ranjit S.; Jha, Rakesh Kumar; Bankar, Nandkishor; Singh, Brij Raj; Ghogare, Ajinkya S.; Patil, Ragini (International Journal of Psychosocial Rehabilitation, 2020)
The psychiatric disorder is classified based on subjective behavioural, mental criteria, which are diagnosed clinically. So, it is difficult to diagnosis and treatment for clinicians. By using of biomarkers; can improve to help and diagnosis disorder.1 Prolactin (PRL) is known versatile hormones. Due to its important role it is considered in the modulation of the stress response, during pregnancy and lactation. The creation of highly sensitive immunometric assays for thyroid-stimulating hormone (TSH) has provided a clearer understanding of thyroid hormone control but has paradoxically led to the kaleidoscopic nature of the thyroid function test variability in hospitalized patients with psychiatric disorder.Role of Prolactin and Thyroid Hormone (T3, T4, TSH) in Psychiatric Disorders.The present study includes total 90 subjects that include 30 healthy individual, 30 Mild Depressive patients and 30 Severe Depressive Patients. Blood samples were collected from the subjects were obtained for Prolactin and Thyroid hormone (T3, T4, TSH) estimation, from Psychiatric Wards. The level of prolactin was statically significant in depressive cases. The mean level of TSH was statistically nonsignificant but the level of total T3 was and total T41 was statistically significant as compared to the controls and that the difference was statistically significant. As per our study findings a research strategy for prolactin studies have important role in the identification of neurotransmitters involved in psychological disorders. Thyroid dysfunction thyroid dysfunction was more commonly seen in patients suffering from Anxiety disorders, Panic disorders, Social phobia, Depression, Bipolar disorders compared to mood disorders and normal subjects. Finally, the inclusion of the prolactin and thyroid profile test among the psychiatric patients may be helpful in the proper management of the cases for clinician.